TRADISI BAYAR ADAT PISUKE TERHADAP PERNIKKAHAN SUKUK SASAK DALAM PERSPEKTIF ANTROPOLOGI HUKUM DAN HUKUM ISLAM - Aisyunnada Makky; Dzulfikar Rodafi; Ibnu Jazari (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The Sasak people have local wisdom and have their own practices in getting married. In the practice of the Sasak tribe there is a process called pisuke. Pisuke is a security deposit that must be paid by the man to the woman's family owned by the Sasak people. This study uses a qualitative approach that can be used to understand the meaning that comes from social problems. The purpose of this study is to describe the traditional pisuke payment at a Sasak marriage in Kediri Selata Village, West Lombok from the perspective of legal anthropology according to Islamic law. The traditional pisuke payment tradition is a traditional payment process before or after the marriage contract. The pisuke tradition is burdened on the men for the cost of the Thanksgiving procession after the marriage contract. The pisuke custom in terms of legal anthropology is how the local community reacts to maintain and preserve the values that exist in the Sasak community. Legal anthropology is inseparable from social values such as the traditional pisuke payment tradition in Sasak marriages. As for the tradition of paying the pisuke custom, from the point of view of Islamic law, it is called 'urf shahih or a habit that is repeated by many people and the rules are accepted by the surrounding community